Phenotypic Correlation Between Body Weight and Linear Body Measurements of Savanna Goats - Khanyisile Shabangu; Kwena Mokoena; Thobela Louis Tyasi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The study investigated the relationship between body weight and linear body measurements to develop a model Savannah goat farmers will use to improve the body weight. The study was conducted at Bosveld Game Breeders using 60 goats of both sexes (7 bucks and 53 does). A total of six variables, including body weight (BW), heart girth (HG), rump height (RH), sternum height (SH), body length (BL), and withers height (WH), were measured. Pearson's correlation and Stepwise regression analysis were performed for data analysis. Correlation findings revealed that BW had a significantly positive correlation (p < 0.01) with HG (r = 0.88), WH (r = 0.80), RH (r = 0.75), BL (r = 0.72), and SH (r = 0.57) in does. While in bucks, BW had a positively high correlation (p < 0.01) with RH (r = 0.99), BL (r = 0.98), SH (r = 0.97), HG (r = 0.97), and WH (r = 0.83). Correlation outcome suggests that HG, WH, RH, BL, and SH might be used to improve the BW of Savanna goats. According to the regression analysis, both bucks and does have a significant contribution (p < 0.05) of BL to BW. Regression results suggest that BL might be used as a single linear body measurement to estimate BW without a weighing scale. The current study might be used to predict the live body weight of animals to support marketing, breeding, feeding, and health services in rural areas.